(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Analysing various fields, associate numbers, events became the need of time and most important step to do anything and hence data science became an important part in every field. Using the concept of data science, the project of Real Estate Price Prediction is built. The motive of creating a project on Real Estate Price Prediction was just to implement the concepts of data science and python language that is used in analysing for designing an application. This was done to get better understanding of the skills that are needed in python language, analysis using data science. The project focuses on the different features and algorithm available in python and data science. In this project various library of python is used to design an attractive, effective, and beautiful project. The project will introduce a Real Estate price estimation system that done estimate based on various mathematical algorithms and tricks and then gives best possible result.So basically, what this application does is identify the need of user in any specific area in Bangalore.